1990
DOI: 10.1007/bf00185416
|View full text |Cite
|
Sign up to set email alerts
|

High resolution 13C-solid state NMR of bacteriorhodopsin: assignment of specific aspartic acids and structural implications of single site mutations

Abstract: Three mutant strains of Halobacterium sp. GRB with the site of mutation in the bacterioopsin gene (PM 326: Asp96----Asn; PM 374: Asp96----Gly; PM 384: Asp85----Glu) were grown in a synthetic medium containing (4-13C)-Asp. The mutant bacteriorhodopsins labeled with (4-13C)-Asp (37%-45%), and owing to the metabolism of Halobacteria also with (11-13C)-Trp (50%-100%), were isolated as purple membranes and 13C Solid State Magic Angle Sample Spinning (MASS) Nuclear Magnetic Resonance (NMR) spectra of the samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…In addition, tbJ¢ mutant, D96N, has the identical chromophore as ~iild.type BR both in the ground state and M [26]. In 0~ur earlier NMR studies [21,22] the spectra of the wildt~pe and the mutant, DgsN, did not differ as regards the it~,Jternal Asp or the Trp resonances. Therefore it is rea-,~ol~able to assume that the conclusions drawn for the ~ssidues Asp ss and Asp :b' also hold true for wild-type l}I~R.…”
Section: Results and Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In addition, tbJ¢ mutant, D96N, has the identical chromophore as ~iild.type BR both in the ground state and M [26]. In 0~ur earlier NMR studies [21,22] the spectra of the wildt~pe and the mutant, DgsN, did not differ as regards the it~,Jternal Asp or the Trp resonances. Therefore it is rea-,~ol~able to assume that the conclusions drawn for the ~ssidues Asp ss and Asp :b' also hold true for wild-type l}I~R.…”
Section: Results and Discussionmentioning
confidence: 83%
“…Three pronoun~d siti~nals are found in the ground state. They have forl~¢rly been assigned to the deprotonated Asp ~-~ (176.3 R)~m) and Asp ~s (173.7 ppm) as well as to the protonated i~sp ~ (170.3 ppm) [20][21][22]. These assignments made ~ls~ of FTIR studios [5] which showed that Asp b ~s is the ~ccnd internal protonated asparti¢ acid in the BR ~r~and state.…”
Section: Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…% shows positive bands at 1765 cm-1 and 1755 cm-a which are characteristic for the deprotonation of Asp residues. Since independent evidence suggests that Asp212 and Asp85 are deprotonated in the ground state this rate must be correlated to the reformation of bR (Gerwert et al 1989;Braiman et al 1988;Engelhard et al 1989Engelhard et al , 1990Siebert et al in preparation): In earlier work using time resolved IR techniques it has been shown that the absorption changes at 1765 cm 1 and 1755 cm -~ are kinetically different and it was argued that these signals are due to two Asp residues which are deprotonated in the ground state Engelhard et al 1985). Since the sign of the amplitudes between 1770 cm-~ and 1745 cm-1 is positive this band is due to a deprotonation and this must necessarily succeed signals which can be explained by a protonation, such as z 2 and z 4.…”
Section: Apparent Rate Constants and Photocycle Intermediatesmentioning
confidence: 99%
“…The results from the research described above on BR as well as a variety of other spectroscopic studies [7,10,39,63,82,108,139,161,162,225]) led by 1990 to the "standard" model of the BR proton pump mechanism" shown in Fig. 13.…”
Section: Early Model Of the Br Proton Pump Mechanismmentioning
confidence: 97%